DESAIN PANTI SOSIAL TRESNA WERDHA “BUDI SEJAHTERA” LANDASAN ULIN, BANJARBARU - Najmina, Hana Nur; Wastuty, Prima Widia (UNIVERSITAS LAMBUNG MANGKURAT, 2022)
Tresna Werdha Nursing home is a social service facility for neglected elderly people, that provides them with a protected home, in an effort to make the life of the elderly more prosperous. However, this can not be considered fulfilled, when the social interaction and activities included in it are not balanced, and the quality of the facilities inside are not worthy/decent. The design of the Tresna Werdha Budi Sejahtera Home is a form of response to the need to improve the quality of existing buildings in fulfilling the capacity, facilities and support in every neglected elderly life to be able to live independently.